2007
DOI: 10.1111/j.1365-2133.2007.07959.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable pulsed light is less painful than light-emitting diodes for topical photodynamic therapy of actinic keratosis: a prospective randomized controlled trial

Abstract: VPL used for MAL-PDT is an efficient alternative for the treatment of AK that results in complete remission and cosmesis equivalent to LED irradiation but causes significantly less pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 41 publications
4
55
0
Order By: Relevance
“…Following this, another split-face study (n=13) reported similar results, with improved appearance of crow’s feet (55% versus 29.5%), tactile skin roughness (55% versus 29.5%), mottled hyperpigmentation (60.3% versus 37.2%), and telangiectasias (84.6% versus 53.8%) in the ALA-IPL group 169. A major advantage of IPL compared with irradiation with a light-emitting diode is less time expenditure and less painful effects of heat delivery due to shorter intense exposure times 170. Clinicians should be aware that heat delivered by IPL may cause destruction of hair follicles, so it should be used with caution, especially in men with facial hair.…”
Section: Pdt In Proliferative Diseasementioning
confidence: 99%
“…Following this, another split-face study (n=13) reported similar results, with improved appearance of crow’s feet (55% versus 29.5%), tactile skin roughness (55% versus 29.5%), mottled hyperpigmentation (60.3% versus 37.2%), and telangiectasias (84.6% versus 53.8%) in the ALA-IPL group 169. A major advantage of IPL compared with irradiation with a light-emitting diode is less time expenditure and less painful effects of heat delivery due to shorter intense exposure times 170. Clinicians should be aware that heat delivered by IPL may cause destruction of hair follicles, so it should be used with caution, especially in men with facial hair.…”
Section: Pdt In Proliferative Diseasementioning
confidence: 99%
“…Babilas et al 2007 (Table II) reported less pain with a variable pulsed light (VPL) device as compared with a light emitting diode (LED) system in MAL-PDT 39 . Of interest, the VPL device used a higher light dose (80 J/cm 2 ) than the LED (37 J/cm 2 ), but with a short pulse duration of 5 ms (total pulse time 355 ms) rather than continuous delivery.…”
Section: Factors Contributing To Pain Associated With Pdtmentioning
confidence: 99%
“…It has been shown that pain intensity depends on the localization [2,3], size [3,4,5], histological type [4], redness [5] and protoporphyrin IX (PpIX) fluorescence [6] of the treated lesion. Also different light sources [7,8,9], fluence rates [6] and photosensitizing agents [10,11] affect the pain additionally.…”
Section: Introductionmentioning
confidence: 99%